2013
DOI: 10.1177/0011392113516985
|View full text |Cite
|
Sign up to set email alerts
|

Intersecting gender with race and religiosity: Do unique social categories explain attitudes toward homosexuality?

Abstract: Although attitudes toward homosexuality have been widely studied over the past 30 years, few studies have scrutinized the interaction effects between gender and race, and gender and religiosity, on attitudes toward homosexuality. This article analyzes US data from the fifth wave of the World Values Survey, collected in 2006 – a nationally representative sample of individuals residing in the United States. Contrary to previous research, no significant interaction is found between gender and race on attitudes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 48 publications
0
7
1
Order By: Relevance
“…As in other studies (Haider-Markel & Joslyn, 2008; Sakalli, 2002), we found that religious leaders who thought of same-sex sexuality as something that people are born with had more favorable attitudes than leaders who thought that it was a result of upbringing or a personal choice. Other studies have demonstrated that women and younger generations had more positive attitudes towards same-sex sexuality compared to men and older generations, respectively (Andersen & Fetner, 2008; Guittar & Pals, 2014; Hicks & Lee, 2006; Kite & Whitley, 1996; Petersen & Hyde, 2011; West & Cowell, 2015); we did not find such differences. It could be that religion trumps the effects of age and gender; given the limited variance, it is also possible that our measures were not sensitive enough to capture differences related to age and gender.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…As in other studies (Haider-Markel & Joslyn, 2008; Sakalli, 2002), we found that religious leaders who thought of same-sex sexuality as something that people are born with had more favorable attitudes than leaders who thought that it was a result of upbringing or a personal choice. Other studies have demonstrated that women and younger generations had more positive attitudes towards same-sex sexuality compared to men and older generations, respectively (Andersen & Fetner, 2008; Guittar & Pals, 2014; Hicks & Lee, 2006; Kite & Whitley, 1996; Petersen & Hyde, 2011; West & Cowell, 2015); we did not find such differences. It could be that religion trumps the effects of age and gender; given the limited variance, it is also possible that our measures were not sensitive enough to capture differences related to age and gender.…”
Section: Discussioncontrasting
confidence: 99%
“…We furthermore assessed the leaders’ ideas about same-sex sexuality and gender nonconformity from the perspective of the law and human rights, also in the context of the protection of religious freedom, offered by the Kenyan Constitution. To deepen our understanding of religious leaders’ perspectives, we explored whether differences in opinions are related to age and sex; these factors have often been associated with perspectives on same-sex sexuality, with women and younger persons usually being more accepting of same-sex sexuality and gender nonconformity, compared to men and older persons (Andersen & Fetner, 2008; Guittar & Pals, 2014; Hicks & Lee, 2006; Kite & Whitley, 1996; Petersen & Hyde, 2011; West & Cowell, 2015), Finally, we explored whether there were differences between religious leaders perspectives based on the familiarity with same-sex sexuality and gender nonconformity. People who knew gay and lesbian persons have generally been found to have less negative attitudes towards same-sex sexuality (e.g., Collier, Bos, & Sandfort, 2012; Graham, Frame, & Kenworthy, 2014; Patrick et al, 2013; Pettigrew & Tropp, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…According to this view, gay men of color are less willing to come out because minority communities are less likely to be accepting of openly gay individuals (Alexander, 2004). Yet, empirical evidence for such suggestions is mixed (Grov, Bimbi, Nanín, & Parsons, 2006;Guittar & Pals, 2014;Herek & Capitanio, 1995;Lewis, 2003;Moradi et al, 2010). Instead, gay men of color's less willingness to "come out" may be more attributable to racism in the gay community and different conceptions of what it means to be "gay" than to the heteronormativity of communities of color (Cohen, 1996;Ibanez, Marin, Flores, Millett, & Diaz, 2009;McBride, 2005).…”
Section: Identities As Declarationmentioning
confidence: 99%
“…Hunter also demonstrates how racism within the LGBT communities and a feeling of social movement squeeze between racial and sexual justice movements contributes to ambivalence among nonwhite LGBTs toward gay marriage. Further, some studies show that racial differences in homophobic attitudes disappear when controlling for religiosity (Guittar and Pals ; Schulte ), suggesting that religion, not race, is driving the association between homophobic attitudes and nonwhites. Still other research calls the very existence of this association into question—Herek and Capitanio () found no black/white difference in approval of homosexuality, while two other studies of LGB experiences of homophobia and heterosexism find no significant black/white differences in terms of encountering stigma (Moradi et al.…”
Section: Race and Homophobiamentioning
confidence: 99%
“…Even assuming that there may be some real racial differences in homophobic attitudes, the exact cause of those differences is unclear. As mentioned above, some attribute the difference to differences in religiosity (Egan and Sherrill ; Guittar and Pals ; Schulte ); in particular, scholars have argued that black nationalism and the historical construction of black masculinity inform the theologically driven homophobia of many black churches in the United States (Lemelle and Battle ; Ward ). Some also point to the politics of respectability (Higginbotham ) in nonwhite communities, black communities in particular, as central to understanding homophobic attitudes (Battle and Ashley ; Cantu et al.…”
Section: Race and Homophobiamentioning
confidence: 99%